(3GdNUNUI aj GdGOGQI GdYGeI Hjf GdfXQjI hGdJWHjb (B/s - (3YHhj, RjO efjQs ((3YeGf(B: s (3OGQ OLdI(B, s, 2006)
(3GdGWGQ GdYGe ddNUUNI , JgjFI GdefGN GdefGSH dJfajP HQGeL GdNUNUI , GdNUNUI , GdNUNUI heTcdI GdHWGdI , GdJNGUjI aj GdCQOf , HQfGeL GdJNGUjI GdCQOfjI JWhQ GdGWGQ GdJTQjYj hGdeDSSj dYedjI GdNUNUI aj GdCQOf , GdCKGQ GdChdjI ddJNGUjI Ydi GdeJZjQGJ GdcdjI hGdLRFjI GdGbJUGOjI hGdGLJeGYjI aj GdCQOfs
(3HjHdjhZQGajG U(B. 163s
Keywords: (3GdEOGQI GdYGeIs; (3GdNhUUIs; (3GdbWGY GdNGUs